Respostas
respondido por:
20
Encontrar o termo a20:
an = a1 + ( n -1 ) . r
a20 = 3 + ( 20 -1 ) . 3
a20 = 3 + 19 . 3
a20 = 3 + 57
a20 = 60
===
Soma:
Sn = ( a1 + an ) . n / 2
Sn = ( 3 + 60 ) . 20 / 2
Sn = 63 . 10
Sn = 630
===
Outro modo de resolver:
Sn = M.n.( n + 1 ) / 2
S20 = 3 . 20 . ( 20 + 1 ) / 2
S20 = 60 . ( 21 ) / 2
S20 = 1260 / 2
S20 = 630
an = a1 + ( n -1 ) . r
a20 = 3 + ( 20 -1 ) . 3
a20 = 3 + 19 . 3
a20 = 3 + 57
a20 = 60
===
Soma:
Sn = ( a1 + an ) . n / 2
Sn = ( 3 + 60 ) . 20 / 2
Sn = 63 . 10
Sn = 630
===
Outro modo de resolver:
Sn = M.n.( n + 1 ) / 2
S20 = 3 . 20 . ( 20 + 1 ) / 2
S20 = 60 . ( 21 ) / 2
S20 = 1260 / 2
S20 = 630
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás